Developing Quartet Card Media for IPAS Learning on Norms and Local Wisdom In Elementary School - Fanny Zahrotun Nadhifa; Riska Anintyawati (Department of Social Studies Education, Faculty of Tarbiyah and Teacher Training, Datokarama State Islamic University of Palu, Central Sulawesi, Indonesia., 2026)
This study aims to develop Quartet Card media for IPAS learning on norms and local wisdom to strengthen cultural understanding and character education among fourth-grade elementary students at SDN 3 Sukosono. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through observation, questionnaires, and pre-test and post-test instruments involving 26 fourth-grade students, with validations conducted by material and media experts. Data analysis used descriptive qualitative and quantitative techniques, including validity, practicality, N-Gain, and Paired Sample T-Test analyses. The findings indicate that the developed media is highly feasible, as reflected by material expert validation (95.38%) and media expert validation (90.76%). Practicality results also showed positive responses from teachers (82%) and students (90.10%). Furthermore, the media effectively improved students’ understanding, demonstrated by the increase in average scores from 50.6 to 88.1, supported by a high N-Gain score (0.77) and a significance value of <0.001. This study highlights the novelty of integrating local wisdom values into Quartet Card-based IPAS learning as an interactive medium that supports culturally responsive learning and strengthens students’ understanding of social norms and character values in elementary education.